Table of Contents (Medical Forum Monthly, 2024)
Evaluation of Predictors for Severity of Dengue Fever at the Beginning of the Disease 2-5 Rakhshinda Jabeen 2. Aftab Ahmed Siddiqui 3. Asif QureshiFrequency of Diaphragmatic Trauma in Fire-Arm Injury of Abdominal Cases and Outcome of its Management 6-9 Shabab Hussain 2. Viqar Aslam 3. Muhammad Sherose Khan 4. Waheed Alam 5. Sajjad Muhammad Khan 6. Waqar Alam JanSignificance of Sonographic Characterization and FNAC of Small Size Thyroid Nodules 10-13 Tanweer Ahmad 2. Nadeem Mehmood Butt 3. S.M.Nasir QadriThe Correlation and Prognostic Significance of ESR and CRP Values with the Severity of Psoriasis with/without Psoriatic Arthropathy 14-16 Bahram Khan Khoso 2. Irfan ShaikhThe Quality of Sleep, Mood Stability and Coping Strategies Among House Officers 17-19 Sarah Shahed 2. Fakhra RiazComparative Study of Efficacy of ORS with Paedicare (Ready to Use Solution) in Gastroenteritis in Children 20-23Muhammad JalalEvaluation of Hearing Impairment in Children of School Going Age 24-26 Itrat Jawed 2. Faheem Ahmed Khan 3. Raana Mahmood 4. Asif Ali Abbasi 5. Asif Uddin AbbasiEfficacy and Safety of Glucantime for Cutaneous Leishmaniasis – Eight Years Experience at A Tertiary Care Hospital of Karachi 27-30 Rabia Ghafoor 2. Bahram Khan Khoso 3. Sobia Fawad HashmiProfile of Psychiatric Patients Attending Outpatient Clinic of a Tertiary Care Hospital, Karachi. 31-34 Ayesha Sarwat 2. Nighat Nisar 3. Faryal NawabAn Observational Study done to Determine the Contrast in Stress Levels between Medical and Non-Medical Students conducted in Different Institutes in Karachi 35-39 Zeba Saeed 2. Maria Atif 3. Bushra BilalFrequency of Pregnancy Following Laparoscopic Ovarian Drilling in Patients with Clomiphene Resistant Polycystic Ovarian Syndrome 40-42 Syed Muhammad Ali 2. Humera Shaheen 3. Sadia NazirOutcome of Posterior Urethral Valves in Public Sector Hospital: Challenges in Management 43-46 Muhammad Kashif 2. Asif Abbas 3. Mukhtar HussainPrevalence of Skin Diseases in Patients Presenting at the Out Patient Department of Isra University Hospital Hyderabad: A Clinical Survey 47-50 Navaid Kazi 2. Uzma Dost Muhammad Rajar 3. Salman Ahmad Farsi KaziThe Profile of Atopic Dermatitis in Out Patient Department of Dermatology Isra University Hospital 51-54 Uzma Dost Muhammad Rajar 2. Navaid Kazi 3. Salman Ahmad Farsi Kazi